Teachers’ Quality of Work Life In Early Childhood Education - Monika, Sesilia (Indonesian Journal of Early Childhood Education Studies, 2017)
The high demand for the education in early childhood is demanding the quality of early childhood program itself, starting from the quality of curriculum, facilities, and infrastructure, and also the quality of teaching, assisting and educating the early childhood students. Early childhood teachers are required to have competence in various fields, including personal, professional, pedagogical and social competence. The aim of this research is to describe teachers’ Quality of Work Life in Early Childhood Education. The concept of teacher quality of work life was measured with a QWL (Indonesian version), which refers to the eight-dimensional construct of Walton and five sub-dimensions of Hackman and Oldham (Walton, 1980). The composition of QWL instrument including a) adequate fair and compensation, b) safe and healthy working condition, c) balance of work and family (non-work-life), d) social integration in the work organization, e) supervisory (the social relevance of work life), f) constitutionalization in the work organization, g) opportunity for career growth, h) opportunity to use and develop human capacities and i) job characteristic. This research uses descriptive statistical analysis method and the results in which shows that the teachers' quality of work life in early childhood education in Jakarta is in the average category. The dimensions of quality of work life, which are included in the high category, are the dimensions of the co-worker, personal development, work-life balance, work culture, supervisory and job characteristic. Otherwise, the dimensions of quality of work life, which are included in the low category, are the dimensions of pay and benefit, promotion and working condition.